USING CROSSWORD PUZZLE GAMES IN INCREASING THE SEVENTH-GRADE STUDENTS' VOCABULARY MASTERY - Sulaiman, Masagus; Hartati, Sri; Tarmizi, M.; Septarini, Dian (Universitas Muhammadiyah Palembang, 2025)
The problem of this research was whether crossword puzzle games effectively increase seventh-grade students' vocabulary mastery at MTs Al-Hidayah of Muara Telang. This research aimed to determine whether crossword puzzle games effectively increase seventh-grade students' vocabulary mastery at MTs Al-Hidayah of Muara Telang. This research used a pre-experimental design. The population of this research was the seventh-grade students of MTs Al-Hidayah of Muara Telang, with a total of 67 students. The sample of this research was 33 students selected through total sampling. The data obtained were analyzed by using a matched t-test for a manual calculation. The result of the t-test calculating in the pre-test and post-test class paired sample t-test showed that the mean was 26,96970, the standard deviation was 12,74383, the standard error mean was 2,21842, the lower was -31,48846, the upper was 22,45093 of t obtained was 12,157. On the other hand, Crossword Puzzle Games effectively increased vocabulary mastery among seventh-grade students at MTs Al-Hidaya of Muara Telang.